Pengaruh Program Karantina terhadap Self-Efficacy Abang None Jakarta Barat 2025 - Alexandre, Reagan; Subroto, Untung (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Self-efficacy is an individual's belief in their ability to organize and carry out the actions necessary to achieve a goal or deal with a particular situation. This study aims to determine the effect of the 2025 West Jakarta Abang None quarantine program on increasing the self-efficacy of the finalists. The study used a quantitative method with a one-group pretest–posttest design without a control group, involving 30 participants (15 Abang and 15 None). The measurement instrument was the General Self-Efficacy Scale (Schwarzer & Jerusalem, 1995). Data analysis was performed using a paired-samples t-test. After analysis, the results were found to be (t(29) = -1.53, p = 0.138; Cohen's d = 0.28), meaning that there was no effect of the quarantine program on the self-efficacy of the 2025 West Jakarta Abang None finalists.